A new vision for the Journal of Management & Organization: The role of context - Galvin, Peter (Cambridge University Press, 2014)
The move by the Journal of Management & Organization (JMO) to Cambridge University Press is significant in a number of ways. It clearly sets JMO on a path of being a significant internationally recognised journal. The number of submissions being received from outside Australia and New Zealand has grown enormously over the past 5 years (to now exceed 80% of all submissions), and along with the internationalisation of the Editorial Board, moving to a leading international publisher sends a very clear signal that JMO is an established international journal with clear growth and reputation oriented ambitions.Perhaps most significantly, the move to Cambridge has coincided with an exciting new focus for 2014 onwards. From this point, the focus for JMO is on context-specific research, recognising the pressing need for outlets for scholarly dialogue from the perspective that ‘context matters’. Tsui (2006: 2) defines contextualisation as ‘incorporating the context in describing, understanding, and theorising about phenomena within it’ and highlights that ‘the need for contextualisation is well accepted’. Nonwithstanding, this recognition, the outlets for research emphasising a contextualisation approach are less clear and hitherto now no dedicated outlet for such research existed.Some globalisation scholars may take the view that the world in becoming more homogeneous, however, I would posit that the world remains close to as heterogeneous as ever, and that it is the level of interconnectedness that is increasing. The growth of economies outside North America and Western Europe has actually reinforced our understanding of this heterogeneity as large multinationals from other regions are increasingly visible on the global stage and are now moving into traditional ‘Western’ markets either directly or through mergers and acquisitions. The economic rise of China, and Asia more generally, and the corresponding shift of economic power away from the West to the East provides just one logic for our need to account for contextual factors to an ever greater extent. More generally, greater scrutiny of so-called universal theories will be required to ascertain which may require replacement by more specific ‘mid-range’ theories that address the particular contextual factors pertinent to organisational phenomena. Further, theories and practices that accommodate different contexts will be essential to underpin the future of management education and practice in a globalised world.